2015
DOI: 10.1097/phm.0000000000000214
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic Assessment of the Femoral Cartilage Thickness in Patients with Pes Planus

Abstract: The distal femoral cartilages of the pes planus patients seem to be thicker, and this finding could possibly stem from excessive mechanical stress on the knee joint caused by impaired lower extremity biomechanics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 18 publications
2
13
0
Order By: Relevance
“…To our knowledge, there is only one published study investigating the changes in femoral cartilage thickness in individuals with flatfoot. Similar to our study, Öztürk et al 24 reported that femoral cartilage thickness at the intercondylar area and the medial condyle were higher in individuals with flatfoot, but both groups had similar femoral cartilage thickness at the lateral condyle. In this study, the increase in femoral cartilage thickness in individuals with flatfoot was associated with changes in lower extremity alignments with flatfoot.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…To our knowledge, there is only one published study investigating the changes in femoral cartilage thickness in individuals with flatfoot. Similar to our study, Öztürk et al 24 reported that femoral cartilage thickness at the intercondylar area and the medial condyle were higher in individuals with flatfoot, but both groups had similar femoral cartilage thickness at the lateral condyle. In this study, the increase in femoral cartilage thickness in individuals with flatfoot was associated with changes in lower extremity alignments with flatfoot.…”
Section: Discussionsupporting
confidence: 91%
“…Similar to previous studies, 29,34 the patellar tendon thickness was performed at the inferior pole of the patella and 1 cm proximal of the inferior pole of the patella (Figure 1B). Similar to previous studies, 15,24 the femoral cartilage thickness was measured with the participants in the supine position with the knee in maximum flexion. For the measurements of the femoral cartilage thickness, the transducer was placed axially above the patellar outer edge.…”
Section: Methodsmentioning
confidence: 80%
See 1 more Smart Citation
“…The CT values from SPV-based measurements in the young asymptomatic participants in this study were similar to those reported in previous studies. 18,22 A significantly lower interrater ICC at the intercondylar groove from SPV-based measurements may indicate the challenge of using this view in patients with symptomatic KOA. As the concavity (or sharpness) of the femoral trochlea increased in the posterior aspect (more caudal), the varying angles of knee flexion in the patient group may have affected the measurements between the raters.…”
Section: Discussionmentioning
confidence: 99%
“…These controversies include the validity and measurement technique for this test. Nevertheless, it has been reported in the literature that US can assess cartilage thickness accurately [7‐13]. Naredo et al [14] also reported that US demonstrated good reproducibility in the measurement of normal to damaged cartilage, although the positioning of the transducer while measuring femoral cartilage thickness has been a matter of debate.…”
Section: Discussionmentioning
confidence: 99%